Teknologi Mesin Penumbuk Udang Rebon Semi Otomatis untuk Pembuatan Terasi di Masyarakat Nelayan Pantai Kenjeran Baru Sukolilo Surabaya - Prasetyawati, Dian; Syahrir, Irwan; Amalia Herdianti, Winda (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
The livelihood of the majority of residents of Sukolilo Baru Subdistrict, Surabaya, is fishing. There are around 126 fishermen in the area whose main catch commodities are sea cucumbers and rebon shrimp. In certain months, namely May, June and July, it is the harvest period for these fishermen where the catch of rebon shrimp is so abundant that on average every fisherman who goes to sea will come home with 40-50 kg of rebon shrimp. One of the processed products The seafood produced from rebon shrimp and currently being developed by local residents is shrimp paste. This shrimp paste is produced using equipment and technology that is still completely manual, namely by pounding it so that it is not optimal to be able to process large quantities of rebon shrimp. In this research, our Research Team will design tools and machines for pounding rebon shrimp with modern, semi-automatic technology that are adapted to the level of needs of the Kenjeran Baru Sukolilo fishing community based on surveys that have been carried out.